The Effect of topical aloe vera on striae gravidarum severity among pregnant women - Sri Wulandari; Witri Lathifah; Marselina Labai Lejau; Nathasya Deshandry Rambu Haima (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Striae gravidarum is one of the most common physiological skin changes experienced during pregnancy, affecting up to 90-95% of pregnant women. It may cause itching, skin irritation, and decreased self-confidence. Aloe vera has been reported to possess moisturizing and skin-regenerating properties that may help reduce the severity of stretch marks during pregnancy. Purpose: This study aimed to determine the effect of aloe vera application on reducing striae gravidarum among pregnant women. Methods: This quantitative study employed a quasi-experimental design using a non-equivalent control group pretest–posttest approach. A total of 37 pregnant women were recruited using total sampling. Aloe vera was applied for four weeks, and observations were conducted before and after the intervention. Data were analyzed using descriptive statistics and the Paired t-test. Results: Most respondents were classified as non-risk age (81.08%) and multiparous (64.86%). Statistical analysis demonstrated a significant reduction in striae gravidarum scores after four weeks of aloe vera application (p= 0.000; p< 0.05), indicating a significant difference between pretest and posttest measurements. Conclusion: Aloe vera application significantly reduced the severity of striae gravidarum in pregnant women after four weeks of intervention. Aloe vera may be considered a safe and affordable complementary intervention for managing stretch marks during pregnancy.